Exploiting Atropisomerism to Increase the Target Selectivity of Kinase Inhibitors. Issue 40 (14th August 2015) - Smith, Davis E.; Marquez, Isaac; Lokensgard, Melissa E.; Rheingold, Arnold L.; Hecht, David A.; Gustafson, Jeffrey L.
Abstract Many biologically active molecules exist as rapidly interconverting atropisomeric mixtures. Whereas one atropisomer inhibits the desired target, the other can lead to off‐target effects. Herein, we study atropisomerism as a possibility to improve the selectivities of kinase inhibitors through the synthesis of conformationally stable pyrrolopyrimidines. Each atropisomer was isolated by HPLC on a chiral stationary phase and subjected to inhibitor profiling across a panel of 18 tyrosine kinases. Notably different selectivity patterns between atropisomers were observed, as well as improved selectivity compared to a rapidly interconverting parent molecule. Computational docking studies then provided insights into the structure‐based origins of these effects. This study is one of the first examples of the intentional preorganization of a promiscuous scaffold along an atropisomeric axis to increase target selectivity, and provides fundamental insights that may be applied to other atropisomeric target scaffolds.